2017
DOI: 10.18632/oncotarget.18727
|View full text |Cite
|
Sign up to set email alerts
|

Association ofTERTpolymorphisms and risk of coronary heart disease in a Chinese Han population

Abstract: Genome-wide association studies have identified that TERT gene was associated with telomere length and age-related diseases. However, little study directly focused on the association between TERT gene polymorphisms and risk of coronary heart disease (CHD). We conducted a case-control study to examine the effect of TERT polymorphisms on CHD risk among 596 CHD patients and 603 healthy controls from China. Five significant single nucleotide polymorphisms (SNP) in TERT were selected and genotyped using Sequenom Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… Locus associated with mLOY? Associations between germline variation in gene and diseases of ageing Associations between somatic gene changes and diseases of ageing TERT Yes Yes Yes Cancer 164 ; CVD 165 167 ; dementia 178 Cancer 179 ; CVD 180 ; dementia 181 , 182 CHEK2 Yes Yes Yes Cancer 120 124 Cancer 183 ATM Yes Yes Yes Cancer 133 138 Cancer 184 TCL1A Yes Yes Yes NA Cancer 185 46/1 haplotype Yes Yes No Cancer 82 84 NA SH2B3 Yes Yes No Cancer 144 ; CVD 153 157 Cancer 144 TET2 Yes No Yes Cancer 141 143 ; CVD 148 Cancer 186 ; CVD 50 , 51 , 54 , 56 , 147 MAD1L1 …”
Section: Overlap With Processes Of Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“… Locus associated with mLOY? Associations between germline variation in gene and diseases of ageing Associations between somatic gene changes and diseases of ageing TERT Yes Yes Yes Cancer 164 ; CVD 165 167 ; dementia 178 Cancer 179 ; CVD 180 ; dementia 181 , 182 CHEK2 Yes Yes Yes Cancer 120 124 Cancer 183 ATM Yes Yes Yes Cancer 133 138 Cancer 184 TCL1A Yes Yes Yes NA Cancer 185 46/1 haplotype Yes Yes No Cancer 82 84 NA SH2B3 Yes Yes No Cancer 144 ; CVD 153 157 Cancer 144 TET2 Yes No Yes Cancer 141 143 ; CVD 148 Cancer 186 ; CVD 50 , 51 , 54 , 56 , 147 MAD1L1 …”
Section: Overlap With Processes Of Ageingmentioning
confidence: 99%
“…Recent work using Mendelian randomization has suggested that the telomere–CH relationship is actually bidirectional: longer telomeres may partly cause CHIP (perhaps through an increased propensity for mutation) whereas CHIP, once acquired, may contribute to telomere shortening (possibly via increased rates of cell cycling) 163 . Importantly, genetic association studies of telomere maintenance genes have revealed links to a broad spectrum of diseases, including strong ties to cancer 164 and CVD 165 168 . Future work investigating links between telomere length and these diseases (or CH and these diseases) may need to account for mediating effects through the telomere–CH axis.…”
Section: Overlap With Processes Of Ageingmentioning
confidence: 99%
“…Our results show that the minor alleles "T" of rs10069690 was associated with a reduced risk of CHD in Han Chinese population. Hongmei H et al [33] showed that the minor allele T of rs10069690 was associated with an increased risk of CHD in some genetic models. We considered that the difference in our ndings from their study can be attributed to sample size, gender and regional difference in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the T allele of rs10069690 was associated with an increased risk of breast cancer [ 12 ], lung cancer [ 19 ], esophageal cancer [ 23 ], gastric cancer [ 25 ], coronary heart disease [ 26 ]. However, rs10069690 was found to be associated with significantly reduced risk of hepatocellular carcinoma, prostate cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%